2018
DOI: 10.1016/j.wear.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of high shear inhibitor performance in CO2-containing flow-induced corrosion and erosion-corrosion environments in the presence and absence of iron carbonate films

Abstract: Evaluation of high shear inhibitor performance in CO2-containing flow-induced corrosion and erosion-corrosion environments in the presence and absence of iron carbonate films. Wear, 405. pp. 143-152.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…The impingement system has been extensively used [17][18][19][20][21][22][23][24][25][26][27] to study the influence of the different parameters on erosion-corrosion. The erosion-corrosion resistance of carbon steel in CO 2 containing environments has also been widely investigated [28][29][30][31]. This paper focuses on the impact of sand loading and velocity on the erosion-corrosion of mild steel by the impingement test in an aqueous slurry.…”
Section: Introductionmentioning
confidence: 99%
“…The impingement system has been extensively used [17][18][19][20][21][22][23][24][25][26][27] to study the influence of the different parameters on erosion-corrosion. The erosion-corrosion resistance of carbon steel in CO 2 containing environments has also been widely investigated [28][29][30][31]. This paper focuses on the impact of sand loading and velocity on the erosion-corrosion of mild steel by the impingement test in an aqueous slurry.…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations were made by Paolinelli et al [7] and Zhang et al [8] who reported that an increase in pre-corrosion time led to a decrease in inhibitor efficiency which was attributed to the formation of corrosion products. However Senatore et al [9] observed a notable synergistic interaction between the inhibitor and the corrosion product in providing protection against erosion-corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, when solid particles are entrained to corrosive flow medium, the pipelines bear erosion and corrosion simultaneously, and erosion-corrosion (E-C) will be aggravated [6,7]. Owing to the synergism between erosion and corrosion, which is the coupling between electrochemical and mechanical processes, it is challenging to authentically grasp the essential origins of the material failure and dependably forecast the lifespan of pipelines [8][9][10].…”
Section: Introductionmentioning
confidence: 99%